(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article focuses on the moral principles M. Gorky stories from the series «In Russia». Given the conflicting views of M. Gorky of morality in society, the author tries to defend the position of the writer’s understanding of the philosophical and ethical problems in his stories.